Methyl jasmonate counteracts cadmium toxicity in water spinach plant by adjusting growth, physiology and redox regulation - Md. Sabibul Haque; Shitosri Mondal; Kh Sabbir Hossain; Artho Baroi; Md. Tanveer Hussain; Md. Ashik Mia; Md. Nesar Uddin; A. K. M. Golam Sarwar; Md. Alamgir Hossain; Md Amirul Islam (Scientific Reports)
Abstract Increased cadmium (Cd) level in foods due to anthropogenic activities is a serious concern to public health. This study investigated the efficacy of exogenous methyl jasmonate (MeJA) application to mitigate adverse effects of Cd toxicity in water spinach plant. The seeds (cv. Gimakolmi) were primed with MeJA (2.5 and 5 µM) and grown under two levels of Cd (10 and 20 µM CdCl2) with or without the respected levels of MeJA solutions under the hydroponic system. The experiment was set in a completely randomized design with three replications maintaining seven growth conditions: (1) Control, (2) Cd10, (3) Cd20, (4) Cd10MJ2.5, (5) Cd10MJ5, (6) Cd20MJ2.5 and (7) Cd20MJ5. Cd-stress significantly hindered growth and photosynthesis; induced oxidative damage accumulating higher malondialdehyde (MDA) and H2O2 contents; enhanced activities of antioxidative enzymes and increased Cd uptake in water spinach plant. The treatments Cd10MJ5 and Cd20MJ5 stimulated plant growth by increasing total dry mass (66% and 38%) and rate of photosynthesis (51% and 55%) of water spinach under two levels of Cd stress, respectively. Application of 5 µM MeJA considerably reduced leaf MDA (32% and 17% compared to Cd10 and Cd20, respectively) and H2O2 contents (49 and 42%) and enhanced the activities of superoxide dismutase (71% and 6%), catalase (120% and 61%) and peroxidase (57% and 65%) enzymes with reduced uptake of total Cd (38% and 45%) in water spinach plant. Conclusively, 5 µM MeJA effectively mitigated Cd toxicity in water spinach plant and can be adopted in Cd-contaminated areas with further field trials.